PARRY-ROMBERG SYNDROME: DIFFICULTIES OF DIAGNOSIS AND IMPROVEMENT OF TREATMENT - Hladka, V.M.; Purdenko, T.Y.; Tarianyk, K.A. (World of Medicine and Biology, 2020)
The article described a case of a rare disease – progressive facial hemiatrophy in a patient of the Neurological Department of Poltava Regional Clinical Hospital. We reviewed a literature on the problem, analyzed the etiological factors, pathogenesis and clinical characteristics of the disease. There was defined a range of necessary examination methods of patients, which included examination by a neurologist, rheumatologist, endocrinologist, as well as the use of additional instrumental and laboratory research methods. Comprehensive treatment tactics include the use of trophotropic, vascular drugs, anabolic hormones, potassium supplements, massage, physical therapy.
Keywords: facial hemiatrophy; Parry-Romberg syndrome; neurodental syndrome